Severe cytomegalovirus infection in immunocompetent patients. - Eddleston, M; Peacock, S; Juniper, M; Warrell, D (1997)
Severe cytomegalovirus (CMV) infection is rare in previously healthy immunocompetent individuals; to our knowledge, only thirty-four such cases have been reported in the worldwide literature. Multiorgan involvement was associated with a high mortality rate among these patients. Disease that clinically involves only the liver or lungs could be fatal; in contrast, none of the patients with isolated central nervous system infection died. Although few patients were treated with specific antiviral therapy, five of six patients with severe infection recovered after receiving therapy with ganciclovir or foscarnet. The rarity of severe CMV disease in immunocompetent patients probably precludes the performance of a clinical trial to evaluate the efficacy of specific antiviral therapy. However, the historically poor prognosis in the absence of such therapy suggests that rapid diagnosis of CMV disease and early instigation of specific treatment may be important.